My love mix-up! Vol. 2 - Hinekure, Wataru (Shojo beat manga., 2022)
When Aoki borrows Hashimoto's eraser, it not only causes talk among his friends, but is at fault for making him flunk a quiz! And Ida is ready to talk about what she and Aoki are to each other.